FINTECH AND FINANCIAL SERVICES TRANSFORMATION: POTENTIAL AND RISKS - Erwin; Noorsidi Aizuddin Mat Noor; Widjanarko; Al-Amin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The technological revolution of the last decade has significantly impacted the financial services industry, characterised by the rise of financial technology (fintech). Fintech has promised to increase accessibility of financial services, transactional efficiency and financial inclusion. However, this rapid growth also brings new risks and challenges that are not yet fully understood. The research method used in this study is literature. The results show that fintech has successfully changed the paradigm of financial services, integrating technologies such as AI, machine learning, and big data analytics to deliver faster, cheaper, and more personalised services. This has contributed to financial inclusion in many previously underserved areas. However, significant challenges such as cybersecurity risks, regulatory uncertainty, and operational risks are emerging as side effects of the rapid adoption of fintech. These risks demand serious attention, mitigation, and management from all decision makers in the industry.